2014
DOI: 10.1088/0004-637x/787/1/16
|View full text |Cite
|
Sign up to set email alerts
|

THE PHYSICAL CHARACTERISTICS OF THE GAS IN THE DISK OF CENTAURUS A USING THEHERSCHEL SPACE OBSERVATORY

Abstract: We search for variations in the disk of Centaurus A of the emission from atomic fine structure lines using Herschel PACS and SPIRE spectroscopy. line ratio, a proxy for the heating efficiency of the gas, shows no significant radial trend across the observed region, in contrast to observations of other nearby galaxies. We determine that 10%-20% of the observed [C ii] emission originates in ionized gas. Comparison between our observations and a PDR model shows that the strength of the far-ultraviolet radiation f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 80 publications
(185 reference statements)
2
21
0
Order By: Relevance
“…Whilst both the number of pixels and their spatial resolution are low, providing only coarse estimates of the local ionised gas contribution to the [C] emission, our values across the disc appear consistent with previous results from a variety of astronomical sources (see e.g. Oberst et al 2006Oberst et al , 2011Croxall et al 2012;Parkin et al 2013Parkin et al , 2014Farrah et al 2013). The small number of low resolution pixels available when using the [N] 205 µm map introduces a problematic limitation to our analysis, particularly evident when we attempt to use these results to correct our observed [C] emission for the contribution arising from ionised gas in order to facilitate a comparison with the Kaufman et al (1999Kaufman et al ( , 2006) PDR model (Sect.…”
Section: Ionised Gas Contribution To [Cii] Emissionsupporting
confidence: 89%
See 4 more Smart Citations
“…Whilst both the number of pixels and their spatial resolution are low, providing only coarse estimates of the local ionised gas contribution to the [C] emission, our values across the disc appear consistent with previous results from a variety of astronomical sources (see e.g. Oberst et al 2006Oberst et al , 2011Croxall et al 2012;Parkin et al 2013Parkin et al , 2014Farrah et al 2013). The small number of low resolution pixels available when using the [N] 205 µm map introduces a problematic limitation to our analysis, particularly evident when we attempt to use these results to correct our observed [C] emission for the contribution arising from ionised gas in order to facilitate a comparison with the Kaufman et al (1999Kaufman et al ( , 2006) PDR model (Sect.…”
Section: Ionised Gas Contribution To [Cii] Emissionsupporting
confidence: 89%
“…we only observe about half of the total [O] 63 µm emission from all PDRs within the PACS beam, Parkin et al (2013Parkin et al ( , 2014 multiply their observed [O] 63 µm emission by a factor of two. This is a conservative correction; Stacey et al (2010) reason that the observed [O] line intensity should be corrected for these geometric issues by as much as a factor of four for high optical depth in a spherical cloud geometry.…”
Section: Adjustments To Observed Quantitiesmentioning
confidence: 85%
See 3 more Smart Citations